Mapping the Germ-Line and Somatic Genomes of a Ciliated Protozoan,Tetrahymena thermophila - Orias, Eduardo (Genome Research, 1998)
Ciliates are among the very few eukaryotes in which the powers of molecular biology, conventional genetics, and microbial methodology can be synergistically combined. Because ciliates also are distant relatives of vertebrates, fungi, and plants, the sequencing of a ciliate genome will be of import to our understanding of eukaryotic biology. Tetrahymena thermophila is the only ciliate in which a systematic genetic mapping of DNA polymorphisms has begun.Tetrahymena has many biological features that make it a specially or uniquely useful experimental system for fundamental research in cell and molecular biology and for biotechnological applications. A key factor in the usefulness of Tetrahymena is the speed, facility, and versatility with which it can be cultivated under a wide range of nutrient conditions, temperature, and scale. This article describes the progress made in genetically and physically mapping the genomes of T. thermophila: the micronuclear (germ-line) genome, which is not transcriptionally expressed, and the macronuclear (somatic) fragmented genome, which is actively expressed and determines the cell’s phenotype.